Dominica : Second Review Under the Stand-By Arrangement, Cancellation of Stand-By Arrangement and Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
In this study, the authorities outlined a two-stage strategy and explained the need for requesting the cancellation of Stand-By Arrangement and the approval of a Three-Year Arrangement Under the Poverty Reduction Growth Facility (PRGF). The objective of the three-year program is to review growth by addressing the debt overhang and structural weaknesses. The underlying concept of fiscal reform is to support the achievement of the medium-term primary surplus target. The authorities will implement a number of initiatives to strengthen the investment climate in the economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet